The role of social institutions in building the youth's social resilience in Bandarharjo, North Semarang - Khoirudin, Iman; Atmaja, Hamdan Tri; Arsal, Triwathy (Universitas Negeri Semarang, 2023)
Social resilience is one of the vital social capitals for youth, especially in Bandarharjo, North Semarang, a marginalized area with many juvenile delinquents. Social resilience is an attempt to transform social behavior in a place that is safe, conducive, and upholds tolerance. Therefore, this article aims to examine the social institution's role in building youths' social resilience in Bandarharjo North Semarang and analyze the youths' social resilience in Bandarharjo with Bourdieu's theory as the leading theory. This research employed a qualitative approach with a phenomenological description study that investigated the individual's subjective experience through the social institution leaders and youths in Bandarharjo. The results showed that the social institutions involved in the establishment of social resilience are family, village community, religious institutions, and educational institutions; youth social resilience predominantly comes from religious and family social institutions; and social resilience can alter most of the negative behaviors of marginalized youth in Bandarharjo and sustain them through internal and external negative influences. This research reinforces Bourdieu's theory that a good environment and social capital affect individuals' habits in developing social resilience.